2019
DOI: 10.1109/access.2019.2957056
|View full text |Cite
|
Sign up to set email alerts
|

Solar Electric Vehicle Energy Optimization for the Sasol Solar Challenge 2018

Abstract: This research combines a set of optimization algorithms with methods of finding and using the expected values of forecasted weather variables to create an optimal speed profile for a solar electric vehicle to minimize energy usage while traveling the furthest distance during the Sasol Solar Challenge 2018 as such work has not been formalized yet. Various Probability Mass Functions describe and apply the probabilistic characteristics of the solar irradiance to the forecasted weather data to increase the probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Figure 4 shows the SCIII solar car followed by its telemetry support vehicle responsible for recording and analyzing data during the SSC 2018 [30]. These mean forecast performance std values subsequently confirm the expected increasing error trend with the increase in cloud cover [21].…”
Section: Energy Forecasting For a Solar Car In South Africamentioning
confidence: 57%
See 4 more Smart Citations
“…Figure 4 shows the SCIII solar car followed by its telemetry support vehicle responsible for recording and analyzing data during the SSC 2018 [30]. These mean forecast performance std values subsequently confirm the expected increasing error trend with the increase in cloud cover [21].…”
Section: Energy Forecasting For a Solar Car In South Africamentioning
confidence: 57%
“…The team had developed an energy simulation platform to assist the energy manager in making informed decisions in regards to the speed and distance they should travel each day based on the dynamics of the car, the route to be driven, the weather conditions, and other characteristics such as remaining stored battery energy. The authors [30] showed simulated SoC results compared to real-life recorded data during the SSC 2018 for SCIII for five of the eight days. The remaining three days' data was not recorded due to technical difficulties.…”
Section: Energy Forecasting For a Solar Car In South Africamentioning
confidence: 99%
See 3 more Smart Citations